2017
DOI: 10.1108/edi-11-2015-0093
|View full text |Cite
|
Sign up to set email alerts
|

Caught between norm and difference: narratives on refugees’ inclusion in organizations

Abstract: Purpose In this study the authors show how discursive spaces both enable and constrain the inclusion of first-generation refugees. For this purpose the authors analyzed a triptych of narratives from first-generation refugees, employers, and mediators (mediating between organizations and job-seeking refugees). The authors adopted a critical studies approach, paying particular attention to the ways in which meanings are embedded within the normalizing discursive processes. The purpose of this paper is to show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 26 publications
3
56
0
5
Order By: Relevance
“…This study adds to employer engagement research by providing empirical evidence concerning refugees, who constitute a particularly vulnerable group. Echoing previous research that pointed out refugees’ relatively poor job quality (Bakker et al, 2017; Colic-Peisker and Tilbury, 2006; Knappert et al, 2018; Ponzoni et al, 2017; Van Tubergen, 2011), our study too identified a large cluster of ‘Bad jobs’, where all job quality dimensions are below average.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This study adds to employer engagement research by providing empirical evidence concerning refugees, who constitute a particularly vulnerable group. Echoing previous research that pointed out refugees’ relatively poor job quality (Bakker et al, 2017; Colic-Peisker and Tilbury, 2006; Knappert et al, 2018; Ponzoni et al, 2017; Van Tubergen, 2011), our study too identified a large cluster of ‘Bad jobs’, where all job quality dimensions are below average.…”
Section: Discussionsupporting
confidence: 55%
“…This research consistently shows that refugees earn lower wages than natives and non-refugee migrants (Bakker et al, 2017; Brücker et al, 2019; Giri, 2018), and that they are more often overqualified for their job (Lamba, 2003; OECD, 2016). Furthermore, there are qualitative studies indicating that refugees feel de-valued at work (Baranik et al, 2018; Eggenhofer-Rehart et al, 2018; Knappert et al, 2018; Ponzoni et al, 2017), and that particularly women experience exclusion at work (Knappert et al, 2018; Tomlinson, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…They demonstrate how organisations can present themselves as inclusive employers and have a range of inclusive practices, yet their inclusion efforts and policies may still be insufficient to address the hierarchies between the groups of employees. Ponzoni et al (2017) also show that in the case of migrant populations, exclusionary elements are still present, despite organisational intentions to include marginal populations. Dahl's (2014) study suggests that organisational policy may even 'make up' a certain category of workers in striving for inclusion, but in spite of this it also shows that employees may avoid or resist these categories that carry unfulfilled promises of inclusion.…”
Section: Doing Inclusion In Organisationsmentioning
confidence: 90%